Structural characterization and magnetic property determination of nanocrystalline Ba3Fe2WO9 and Sr3Fe2WO9 perovskites prepared by a modified aqueous sol–gel route. Issue 2 (5th December 2018) - Bijelić, Jelena; Stanković, Anamarija; Matasović, Brunislav; Marković, Berislav; Bijelić, Mirjana; Skoko, Željko; Popović, Jasminka; Štefanić, Goran; Jagličić, Zvonko; Zellmer, Sabrina; Preller, Tobias; Garnweitner, Georg; et al.
Abstract : Characterization of nanocrystalline triple perovskites synthesized by a novel modified sol–gel route instead of bulk materials synthesized by a solid-state route. Abstract : Sr3 Fe2 WO9 and Ba3 Fe2 WO9 triple perovskites have been prepared in nanocrystalline form using a modified sol–gel route with citric acid as a chelating agent. These materials have been studied by X-ray powder diffraction (PXRD), energy-dispersive X-ray (EDX) spectroscopy, transmission electron microscopy (TEM), scanning electron microscopy (SEM), and unpolarized Raman spectroscopy, while their magnetic properties have been determined using SQUID measurements. At room temperature, the crystal structure of 6H-perovskite Ba3 Fe2 WO9 is hexagonal, space group P 63 / mmc, with a = 5.7577(2) and c = 14.1095(5) Å, whereas Sr3 Fe2 WO9 presents a tetragonal lattice, space group I 4/ m, with a = 5.5803(1) and c = 7.8745(3) Å. Both compounds are nanocrystalline with average crystallite sizes of 25.6(1) nm for Ba3 Fe2 WO9 and 35.9(1) nm for Sr3 Fe2 WO9 with moderate microstrain. They exhibit a disordered perovskite structure, in which Fe 3+ and W 6+ cations distribute randomly at the B-sites of the perovskite lattice: Sr2 [Fe0.72 W0.28 ] 2a [Fe0.61 W0.39 ] 2b O6 and Ba6 [Fe1.71 W0.29 ] 2a [Fe2.29 W1.71 ] 4f O18 . The detected hysteresis loops with non-zero remanent magnetization and a rather large coercive field reveal ferrimagnetic ordering with ordering temperatures of 373 K for Sr3 Fe2 WO9 and 330 K for Ba3 Fe2 WO9 . Magnetic measurements show the onset of ferrimagnetic ordering at relatively high temperatures of 717 and 711 K for the Sr and Ba compounds, respectively; however the magnetization isotherms at 2 K exhibit, for H = 50 kOe, maximum magnetization values close to 0.8 μ B (f.u.) −1 and 0.35 μ B (f.u.) −1 for Sr and Ba compounds, respectively, although full saturation is not reached.